Osmunda regalis (Osmundaceae) – a new species to the flora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: Is there Osmunda regalis in the flora of Ukraine? What is the current spatial distribution and state of O. regalis populations in Ukraine? Location: Tsumanska Pushcha Kivertsivskyi National Nature Park, Volyn Region, Ukraine. Materials and methods: field surveys, morphological description, phytoindication. Nomenclature: POWO 2025 Results: Osmunda regalis is a fern distributed in Atlantic and sub-Atlantic parts of Europe, Mediterranean, the Balkan Peninsula, and the Caucasus. In Central and Eastern Europe, this species occurs more rarely. According to the last checklists and other publications, O. regalis is absent in the flora of Ukraine. Nevertheless, the nearest population of this fern is quite close to Ukraine and is less than 0.5 km away from the border. Some authors assumed that O. regalis could potentially grow in adjacent territories of Ukraine, but previous investigations were resultless. In 2023, the first individual of O. regalis was revealed in Tsumanska Pushcha National Nature Park in Kivertsi (Kivertsivskyi District, Volyn Region). In 2024, the second one was found in the surroundings. Today, the population is represented by two individuals. Both of them are fertile and can produce spores. The population was discovered in a 30-years-old pine-birch secondary forest with low phytodiversity richness. The species was revealed in the plant community with narrow amplitudes of ecological tolerance. The habitat has wet soil conditions, acidic and poor on mineral nutrients (including nitrogen) sod-podzolic soils. Ombroregime is sub-aridic and the climate continentality regime is between hemi-oceanic and sub-continental. Among studied factors, soil acidity, nitrogen content in the soil, and climate humidity (ombroregime) were extremely limiting factors for that plant community. Such conditions indicate the revealed population is vulnerable because the plants grow on their ecological tolerance limit. Today, only one population, consisting of two individuals, is known to Ukraine. Considering that, O. regalis is recognised as a critically endangered (CR; B2ac(iii, iv) + D) plant species to the flora of Ukraine and should be included in the next edition of the Red Data Book. Because the studied species is the new one to the flora of Ukraine, there are morphological description of O. regalis and the key to identification in the article.
Keywords: biodiversity, ferns, rare species, chorology, morphology, new locations, Polissian Lowland, Tsumanska Pushcha Kivertsivskyi National Nature Park